A integração das tecnologias da informação e comunicação ao currículo no PROEJA - Fernandes, Jarina Rodrigues (2012)
This research aims to identify ways to use the strategic potential of information and communication technologies (ICT) in order to build an integrated curriculum within the National Program for Integration of Professional Education with Basic Education, in the form of youth and adults Education (PROEJA). Before this challenge, it was sought in a first stage of research to critically understand the meanings of integration, curriculum and the presence / role of technology in the curriculum, specifying how they are considered in the base document of PROEJA, directed to technical professional education at average level / high school and the technical quality course plan, in the PROEJA form, from the São Paulo's campus of the Federal Institute of Education, Science and Technology of São Paulo.In a second stage, it was sought to create a critical collaboration context with the teacher of the investigated Computing course. This activity was expanded to other teachers in search of ways to share and build new meanings on the integration of technology into the curriculum of this course.The theoretic-methodological contributions of this research present characteristic of bricolage: to perform the documents analysis, it was employed thematic maps to support bakhtinian's technology and contributions, as well as principles and procedures of the Critical Research Collaboration to the development and analysis of the interaction along with the research subjects.The analysis of the base document points to the defense of an integrating education of basic education and professional education, with references of critical character, to the role of technology in society and in the curriculum. The analysis of the course plan introduces references to the integration and use of technologies with little emphasis on the operationalization of the integrated curriculum and the role of ICT.The analysis of the interaction to the subjects of research shows diverse meanings related to the integration of ICT into the curriculum of the investigated course. The critical-collaborative research conducted with the Computing teacher pointed to the relevance of: articulate the work with both theoretical and practical knowledge in dealing with ICT and create active role opportunities in the process of knowledge construction for the learners. In terms of challenges it has been identified the need for: reconsider the teacher-student relationship, cognize new methodologies aimed at teaching-researchteaching curriculum and other curriculum practices experienced in the other course disciplines.This last challenge conducted the expansion of the research activity to the other teachers of the course, which showed signs of integrating ICTs to the curriculum of several disciplines in which they were used: applications and software, audio, video, animations, teaching materials available on the web; virtual learning environment integrated to the classroom and research on the Internet. To improve such signals of integration it was raised the possibility of: partnerships between the work of the various disciplines and Computing discipline; involvement of technical staff in the process, the organization of a virtual learning environment for PROEJA; exchanges with students from other federal campuses, creation of a virtual space to publish routes and results of projects developed in the course. Before these possibilities, there were raise the difficulties related to the dynamic of class allocation and the lack of staff meetings per course. As a difficulty-possibility, there was raised the creation of spaces for dialogue between PROEJA teachers, a required activity to fulfill the integration of ICT and the curriculum in the mentioned course